Innovation Leadership of Administrators and Relationship with Information and Communication Technology Integration in Seremban of Negeri Sembilan State - Chaw Wei Yeong, Mohd Izham bin Mohd Hamzah (International Journal of Advanced Science and Technology, 2020)
This study aims to identify the level of innovative leadership of administrators in school and thelevel of ICT integration in school. This research explores the relationship between the practice ofinnovative leadership of administrator and the ICT integration. This research is quantitativeresearch with surveying method by using a questionnaire as a research instrument. The leadershipquestionnaire is adapted from Gliddon’s Innovative Leadership Model to test the level ofinnovative leadership while Model SAMR was adapted to test the ICT integration. The respondentswere 234 administrators from 109 primary school in the district of Seremban of Negeri Sembilanstate. A descriptive and inferential analysis was used to test questions study using SPSS. Theoverall finding shows that innovative leadership of administrators is at a very high level and levelof ICT integration presented at a high level. Pearson correlation test found that there was amoderately positive relationship between innovative leadership of administrators and ICTintegration